Digitalisasi Sistem Pelaporan Publik Real-Time Untuk Penguatan Etika Jaksa Berbasis Whistleblowerprotection Dalam Smart Governance - Ismail Hasan Athoillah (Jurnal Hukum Lex Generalis, 2025)
The increasing violations of prosecutors’ code of ethics have led to a decline in public trust toward the Prosecutor’s Office. This study analyzes the public reporting system (whistleblowing system) in Indonesia through the Prosecutors Commission as an external supervisory body and compares it with South Korea. The research employs statute approach, conceptual approach, and comparative approach. The study finds that Indonesia’s reporting system, regulated under the Prosecutors Commission Regulation Number PER-05/KK/04/2012, remains conventional or semi-digital and has not fully supported the concept of smart governance. In contrast, South Korea, as a best practice through the ACRC under the Public Interest Whistleblower Act, provides a transparent, accountable, and participatory oversight mechanism. The implementation of an integrated digital system is expected to enhance the effectiveness of supervision over prosecutors while upholding the ethical standards of the profession.